Lhermitte-duclos disease related with cowden syndrome mimicking metastatic lung cancer on FDG PET/CT - KESİM, SELİN (My University, 2023)
Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.ABSTRACT: Cowden syndrome is characterized by multiple hamartomatous and neoplastic lesions including Lhermitte-Duclos disease, which is the main criterion for the diagnosis. Herein, we presented a patient with suspected metastatic disease referred to PET/CT, which showed mildly hypermetabolic multinodular thyroid goiter, multiple hamartomatous pulmonary, and breast nodules. Also, intense hypermetabolism was noted on the cerebellar tumor lesion. Lhermitte-Duclos disease was diagnosed based on the characteristic MRI findings, and she was followed up with a diagnosis of Cowden syndrome. Our case indicates that Cowden syndrome should be included as a differential diagnosis of abnormal FDG uptake in the multiple systemic hamartomatous tumors.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging; Cowden syndrome; Lhermitte-Duclos disease